Workforce Gaps in Medical Record Personnel Across Healthcare Facilities in Bali Province: Evidence and Policy Implications - Dewi, Luh Deayu Krisna (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
Medical Record and Health Information (MRHI) professionals are recognized as part of the healthcare workforce as stipulated in Law Number 17 of 2023. The implementation of Electronic Medical Records (EMR), mandated through Minister of Health Regulation Number 24 of 2022, requires the availability of competent MRHI personnel in every healthcare facility. This study aims to analyze the gap between the demand for and availability of MRHI professionals in Bali Province. This research employed a descriptive-exploratory approach using secondary data from the Central Bureau of Statistics (BPS), Bali Provincial Health Profile, and the Higher Education Database (PD-DIKTI) for 2024. The estimation of demand was calculated based on the number and type of healthcare facilities and the standard staffing requirements for MRHI professionals. The findings show that the estimated demand reached 1,020 professionals, while the annual availability of graduates who are eligible to work and possess a registration license (STR) is projected to be only around 230 individuals. This gap highlights the urgent need for structured and data-driven health workforce planning. The results of this study may serve as a basis for policy formulation in education, workforce distribution, and the strengthening of digital health service systems at the regional level.